Barriers and Challenges for Technology Transfer in Malaysian Small and Medium Industries - M.A., Burhanuddin; Fahmi, Arif; Anton, S P (Singapore Institute of Electronics, 2009)
Small and medium-scale industries (SMI) have played a very important role in Malaysian economy. Particularly in terms of employment generation, better income distribution and as a training ground for entrepreneurs before investing in a larger scale businesses. However, there are many factors inhibiting the adoption of new technologies especially related to Information and Communication Technology (ICT) in the challenging world today. It is important to identify the primary obstacles they face with regard in adopting new technology. In order for them to survive in a long run, this study identifies problems and constraints faced by SMI in Malaysia. Then, focus on the challenges and barriers for them in adopting new technology. The researchers visited few food-processing SMI in the Southern Region of Malaysia and make comparison with few important publications on SMI development.